2013
DOI: 10.4028/www.scientific.net/aef.8-9.370
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Degradation of Pharmaceutical Compounds as Tetracycline in Aqueous Solution with BDD Electrode

Abstract: Abstract. Antibiotics named tetracycline (TC) are the most popular group of pharmaceutical compounds used in therapeutic purpose in human and veterinary medicine and in aquaculture, due to their characteristics as broad spectrum antibiotic. The tetracyclines are a group of natural and semisynthetic products that are bacteriostatic agents with activity against a wide variety of organisms, but of limited use today because of acquired resistance. Even at low concentrations, tetracycline and its metabolites may ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Studies have shown that conventional WWTPs are inefficient in removing the wide variety of antimicrobial residues in wastewater and may convert them into other chemical forms (treatment TPs). Remaining residues and treatment TPs are released together to the aquatic environment via effluent discharge. , Conventional biological treatments, additional treatment steps such as removal by adsorption and filtration, , and several more advanced treatment techniques (e.g., advanced oxidation, reverse osmosis, or electrochemical degradation ) have been investigated, but complete removal of the entire suite of antimicrobial classes by one single treatment method remains challenging. Owing to inefficient treatment methods and the fact that 44% of domestic wastewater is still not safely treated globally, many studies have reported the presence of antimicrobial parent compounds and related TPs in aquatic environments worldwide. As the COVID-19 pandemic only slowly recedes, the occurrence of antivirals used for treating COVID-19 and their TPs in water is also expected …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that conventional WWTPs are inefficient in removing the wide variety of antimicrobial residues in wastewater and may convert them into other chemical forms (treatment TPs). Remaining residues and treatment TPs are released together to the aquatic environment via effluent discharge. , Conventional biological treatments, additional treatment steps such as removal by adsorption and filtration, , and several more advanced treatment techniques (e.g., advanced oxidation, reverse osmosis, or electrochemical degradation ) have been investigated, but complete removal of the entire suite of antimicrobial classes by one single treatment method remains challenging. Owing to inefficient treatment methods and the fact that 44% of domestic wastewater is still not safely treated globally, many studies have reported the presence of antimicrobial parent compounds and related TPs in aquatic environments worldwide. As the COVID-19 pandemic only slowly recedes, the occurrence of antivirals used for treating COVID-19 and their TPs in water is also expected …”
Section: Introductionmentioning
confidence: 99%
“…Remaining residues and treatment TPs are released together to the aquatic environment via effluent discharge. 9 , 10 Conventional biological treatments, additional treatment steps such as removal by adsorption 11 13 and filtration, 14 , 15 and several more advanced treatment techniques (e.g., advanced oxidation, 16 18 reverse osmosis, 19 21 or electrochemical degradation 22 24 ) have been investigated, but complete removal of the entire suite of antimicrobial classes by one single treatment method remains challenging. 25 27 Owing to inefficient treatment methods and the fact that 44% of domestic wastewater is still not safely treated globally, 28 many studies have reported the presence of antimicrobial parent compounds and related TPs in aquatic environments worldwide.…”
Section: Introductionmentioning
confidence: 99%